2015
DOI: 10.1007/s13762-015-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, thermodynamics and competitive adsorption of lead and zinc ions onto termite mound

Abstract: The elemental composition of termite mound was determined by XRF which revealed K, Ti and Mn as minor constituents while Ca and Fe as major constituents. The DG value for Zn(II) is positive in both single and binary systems, while that for Pb(II) was positive between 313-333 and 323-333 K for single and binary systems, respectively. The data show that the use of neglected termite mound for Pb(II) and Zn(II) removal from aqueous solutions is economically significant in wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…where qe = is the amount of Pb (II) ion adsorbed from the solution in (mg/g) at equilibrium, 𝐶𝑖 = the concentration before adsorption (mg/L), 𝐶𝑒 = the concentration after adsorption (mg/L), V = volume of the adsorbate (L), and M = is the weight in a gram of the adsorbent (g) respectively (Abdus-Salam and Bello, 2015). The extent of adsorption was calculated using the eq.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…where qe = is the amount of Pb (II) ion adsorbed from the solution in (mg/g) at equilibrium, 𝐶𝑖 = the concentration before adsorption (mg/L), 𝐶𝑒 = the concentration after adsorption (mg/L), V = volume of the adsorbate (L), and M = is the weight in a gram of the adsorbent (g) respectively (Abdus-Salam and Bello, 2015). The extent of adsorption was calculated using the eq.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…High Al, Ti, and Fe oxide mineral contents of termite mounds enhace adsorption of contaminants. Termite mounds have been successfully used to remove chromium [46], lead [47], zinc [48], and polycyclic aromatic hydrocarbons (PAH) [49]. Northwestern Ethiopia is characterized by large basaltic dykes as observed by ASTER multispectral imagery [50].…”
Section: Underground Water Treatment and Water Surveymentioning
confidence: 99%
“…The results from their experiment revealed that termite mound materials adsorbed Pb(II) up to 15.5 mg/g, and they then concluded that termite mound soil material is an efficient adsorbent of oxides of metals and even manganite silicate. Additionally reported in literature is the use of termite mound materials for defluoridation [74], the removal of arsenate from water [75], Zn(II) removal from aqueous solutions [76], the removal of dyes from wastewater [77], and the removal of chromium from aqueous solutions [78].…”
Section: The Role Of Termite Mound Soil and Its Bacteria In Bioremedimentioning
confidence: 99%